The character and competitiveness of cooperative banks in Poland - Musialik , Klaudia (Journal of Finance and Financial Law, 2019)
Cooperative banking is perceived mostly as a low-level traditional local banking. Therefore, the topic of the article was taken to show it is competitiveness in various areas. The aim of the article is to show the differences and similarities between cooperative banks and commercial banks and credit unions. Selected statistical data on these institutions was also presented. In addition, the author's intention was to examine the degree of competitiveness of cooperative banking. The author in the article was verifying the hypothesis that the most competitive among cooperative banks, commercial banks and credit unions are cooperative banks, which is assessed by customers in the perspective of their satisfaction. The research was conducted using a questionnaire. It showed that in the opinion of customers there are both prosperous areas of financial institutions and those that need improvement.